Detecting Multiple Structural Breaks in Systems of Linear Regression Equations With Integrated and Stationary Regressors - Karsten Schweikert (Oxford Bulletin of Economics and Statistics, 2025)
In this paper, we propose a two-step procedure based on the group LASSO estimator in combination with a backward elimination algorithm to detect multiple structural breaks in linear regressions with multivariate responses. Applying the two-step estimator, we jointly detect the number and location of structural breaks and provide consistent estimates of the coefficients. Our framework is flexible enough to allow for a mix of integrated and stationary regressors, as well as deterministic terms. Using simulation experiments, we show that the proposed two-step estimator performs competitively against the likelihood-based approach in finite samples. However, the two-step estimator is computationally much more efficient. An economic application to the identification of structural breaks in the term structure of interest rates illustrates this methodology.
Keywords: 330; cointegration; LASSO; model selection; multivariate; shrinkage